Structural Health Monitoring in Civil Engineering Using IoT Sensors (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
Structural Health Monitoring (SHM) using Internet-of-Things (IoT) technology enables continuous, real-time assessment of infrastructure performance and safety. With aging bridges, buildings, and pipelines facing deterioration and unexpected loads, IoT sensor networks provide timely data on vibrations, strains, and environmental conditions to detect damage early This report reviews the principles of IoT- enabled SHM in civil engineering. We examine various sensor types (e.g: accelerometers, strain gauges, fiber-optic sensors), communication technologies (Wi-Fi, ZigBee, LoRa, NB-IoT), and data processing methods including edge computing and cloud analysis. The methodology outlines phases of deployment (planning, installation, data acquisition, analysis) and typical network architectures. Challenges such as power supply, network reliability, and harsh environments are discussed. Finally, future trends like AI-driven damage detection and digital twins are highlighted as ways to improve predictive maintenance of civil infrastructure. In construction industry maintenance should be given utmost importance and focus. For continuous monitoring of maintenance Internet of Things (IoT) can be used. IoT can be used to monitor the structure from anywhere. Structural health monitoring using IoT is the latest technique employed all over the world, especially the buildings exposed to harsh environments. Sensors were used to collect the data from the structure from which we can identify the deterioration and the method to rectify. Cloud computing technique was also employed. A simple signal processing technique helps us to interact with buildings, which was the blessing of IoT. This paper presents the state of art survey about current research and implementations put into practice
Keywords: Structural Health Monitoring (SHM); Internet-of-Things (IoT)